LittoSIM-GEN: A generic platform of coastal flooding management for participatory simulation. (March 2022) - Laatabi, Ahmed; Becu, Nicolas; Marilleau, Nicolas; Amalric, Marion; Pignon-Mussaud, Cécilia; Anselme, Brice; Beck, Elise; Bertin, Xavier; Monfort, Amélie; Hayoun, Clarisse; Rousseaux, Frédéric
Abstract: Coastal flooding is among the most significant disasters that threaten littoral populations in today's world. Climate change and global warming increase this risk and require implementing efficient strategies to anticipate the hazard and reduce human and material damage. This paper describes a generic platform called LittoSIM-GEN (a coupling of agent-based and hydrodynamic models), which aims to involve stakeholders in a participatory simulation of land use management to minimize the risks of coastal submersion. An application to the southwest coast of France (Rochefort) demonstrates the features of this platform. We propose several recommendations to improve the generic conception and implementation of models dedicated to participatory simulation. Highlights: We describe LittoSIM-GEN, a generic model and platform for conducting workshops on flooding risk management. We present an application of LittoSIM-GEN to the case study of Rochefort on the southwest coast of France. We discuss the genericity problem in participatory simulation models.